Ammonium Nitrate as an Eco–Friendly Oxidizer for Composite Solid Propellants: Promises and Challenges. Issue 6 (2nd November 2017) - Jos, Jisna; Mathew, Suresh
ABSTRACT: Ammonium nitrate (AN) has received attraction globally not only as a nitrogenous fertilizer but also as an oxidizer in gas generators and propellants. Nowadays, great attention is being focused on the development of composite solid propellants with green oxidizers in realizing eco–friendly combustion products. The ammonium perchlorate (AP), which is the work horse oxidizer in composite propellant, needs replacement due to its environmental and human health issues. In this context, AN is regarded as an alternative to AP because of its easy availability and environmentally friendly chlorine free combustion products. However, AN has its own inherent drawbacks such as hygroscopicity, room temperature phase transition, and low burning rate. Recently, several studies have been focused on its phase stabilization and burning rate modification so as to develop solid propellants with improved properties. The knowledge of thermal characteristics of AN is a crucial factor for its applications in propellants and gas generators. This article details the different aspects of polymorphism, phase stabilization, thermal decomposition, hygroscopicity, specific impulse, and burn rate modification of AN and also addresses ways to overcome the inherent weakness of AN as a propellant oxidizer in formulating an effective propellant composition.